Leaving everything most loved [large type] : a novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel., 2013)
London, 1933. Two months after the body of an Indian woman named Usha Pramal is found in the brackish water of a South London canal, her brother, newly arrived in England, turns to Maisie Dobbs to find out the truth about her death. Not only has Scotland Yard made no arrests, evidence indicates that they failed to conduct a full and thorough investigation.